FORMULATION AND EVALUATION OF HERBAL GELCONTAINING FENUGREEK AND BRAHMI EXTRACTS FOR THE TREATMENT OF DANDRUFF (International Journal of Food and Nutritional Sciences, 2022)
Human body, have fewer side effects, and are more effective than synthetic drugs, herbal formulations for primary healthcare are in high demand worldwide, particularly in India. A wide range of products, including preparations for skin and hair care, use gels. The goal of the current study is to create and assess an herbal hair gel for the treatment of dandruff using aqueous extracts of fenugreek, neem, and hibiscus as well as various concentrations of Carbopol 934 as the gel base. Herbal gel was assessed based on a few factors, including its physical appearance, pH, homogeneity, Spreadability, viscosity, extrudability, and anti-fungal activity. Different formulations were made and compared and the best formulation was evaluated.